Genome-Wide Identification of Sequence Variations and SSR Marker Development in the Munake Grape Cultivar - Zhong, Haixia; Zhang, Fuchun; Zhou, Xiaoming; Pan, Mingqi; Xu, Juan; Hao, Jingzhe; Han, Shouan; Mei, Chuang; Xian, He; Wang, Min; Ji, Jiahui; Shi, Wei; et al. (Frontiers in Ecology and Evolution, 2021)
The Munake grape cultivar produces uniquely flavored and high-quality fruits. Despite the numerous beneficial agronomic traits of Munake, there are few genetic resources available for this cultivar. To address this knowledge gap, the entire genome was sequenced using whole-genome sequencing approaches and compared with a Vitis vinifera L. reference genome. This study describes more than 3 million single nucleotide polymorphism (SNP), 300,000 insertion and deletion (InDel), 14,000 structural variation (SV), and 80,000 simple sequence repeat (SSR) markers (one SSR per 4.23 kb), as well as their primers. Among the SSRs, 44 SSR primer pairs were randomly selected and validated by polymerase chain reaction (PCR), allowing discrimination between the different Munake cultivar genotypes. The genetic data provided allow a deeper understanding of Munake cultivar genomic sequence and contribute to better knowledge of the genetic basis behind its key agronomic traits.